New Linked Data on Research Investments: Scientific Workforce, Productivity, and Public Value - Julia Lane; Jason Owen-Smith; Rebecca Rosen; Bruce A. Weinberg (Institute for the Study of Labor (IZA), 2014)
Longitudinal micro-data derived from transaction level information about wage and vendor payments made by federal grants on multiple U.S. campuses are being developed in a partnership involving researchers, university administrators, representatives of federal agencies, and others. This paper describes the UMETRICS data initiative that has been implemented under the auspices of the Committee on Institutional Cooperation. The resulting data set reflects an emerging conceptual framework for analyzing the process, products, and impact of research. It grows from and engages the work of a diverse and vibrant community. This paper situates the UMETRICS effort in the context of research evaluation and ongoing data infrastructure efforts in order to highlight its novel and valuable features. Refocusing data construction in this field around individuals, networks, and teams offers dramatic possibilities for data linkage, the evaluation of research investments, and the development of rigorous conceptual and empirical models. Two preliminary analyses of the scientific workforce and network approaches to characterizing scientific teams ground a discussion of future directions and a call for increased community engagement.
Keywords: C8; O3; J4; 330; UMETRICS; STAR METRICS; Science of Science Policy; linked data; scientific workforce; scientific networks